Stimulation of osteoblast activity by induction of Aloe vera and xenograft combination - Utari Kresnoadi; Retno Pudji Rahayu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Tooth extraction is generally followed by alveolar ridge resorption that later can cause flat ridge. Aloe vera have biogenic stimulator and hormone activities for wound healing. Purpose: This study was aimed to know osteoblast activities in alveolar bone after induction of Aloe vera and XCB combination. Methods: Fifty four of Cavia cabaya were divided into three main groups. Group I was control group. Group II was filled with xenograft concelous bovine (XCB) and group III was filled with the combination of Aloe vera gel and XCB. Then, each group was divided into three sub groups according to timing, they are 14, 30, and 60 days after tooth extraction and application. Histology and morphology examination were performed on the harvested specimens. Results: There were significant differences between the control group and the other groups filled with the combination of Aloe vera and XCB. Conclusion: In conclusion, the application of Aloe vera gel and xenograft combination decrease the number of osteoclast and increase the number of osteoblast in post tooth extraction alveolar bone structure indicating the new growth of alveolar bone.Latar belakang: Pencabutan gigi pada umumnya selalu diikuti resopsi tulang alveolar, sehingga bila terjadi dalam waktu yang lama ridge akan menjadi flat. Aloe vera adalah bahan stimulasi biogenik dan mempunyai aktivitas hormon untuk proses penyembuhan luka. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui aktivitas osteoblas pada tulang alveol dengan pemberian kombinasi Aloe vera gel dan xenograft concelous bovine (XCB). Metode: Lima puluh empat ekor Cavia cabaya, dibagi menjadi 3 kelompok besar, kelompok pertama adalah kelompok kontrol yaitu hanya dilakukan pencabutan saja tanpa perlakuan, kelompok ke-2 yaitu kelompok yang setelah dicabut diberi XCB saja dan kelompok ke-3 yaitu kelompok yang setelah pencabutan diberi kombinasi Aloe vera gel dengan XCB pada luka bekas pencabutan gigi. Kemudian masing-masing kelompok besar ini dibagi lagi berdasarkan waktu menjadi 3 sub kelompok yaitu setelah 14, 30 dan 60 hari. Kemudian dilakukan pemeriksaan histology dan morfologi pada specimen hewan coba. Hasil: Terdapat perbedaan bermakna antara kelompok kontrol dan kelompok yang diberi kombinasi Aloe vera dan XCB. Kesimpulan: Disimpulkan bahwa pemberian kombinasi Aloe vera gel dan xenograft menyebabkan penurunan jumlah osteoklas dan peningkatan jumlah osteoblas pada struktur tulang alveol pasca pencabutan gigi yang menunjukkan adanya pertumbuhan tulang alveol baru.